13 Outcome of children with congenital heart disease transferred from their regional paediatric cardiac intensive care unit (pcicu) to a unit with transplant and mechanical support capability. (2nd February 2018) - Cardoso, B; Simpson, E; Llevadias, J; Chilà, T; Guillèn, M; Thiru, Y; Reinhardt, Z; Rita, F De; Hasan, H; Crossland, D
Abstract : Purpose: We describe the management and outcome of children with congenital heart disease (CHD) who exhaust conventional options and require acute transfer to a PCICU with transplant and mechanical support capability. Methods: Retrospective analysis of the patient records (January 2011 – August 2017). Patients with cardiomyopathy were excluded. Results: Thirty patients were transferred, median age 9.2 months (IQR 4.2–39.5 months). Overall survival was 80% at 1 month and 67% at end of study. Ten (33%) had univentricular physiology. Eight (27%) were transferred on ECMO. Nineteen patients were listed for transplant (13 transplanted, 6 deaths on waiting list). Of these, 3 died post-transplant and 7 were bridged with VAD. In eight patients conventional management was considered the best option (6 cardiac surgery, 2 ECMO wean); all survived. Two patients on ECMO had 'bail-out' surgery in an attempt to improve haemodynamics to either allow weaning from ECMO or create a circulation suitable for VAD implant. Both patients died from ECMO complications. One patient was unsuitable for any intervention. There was no difference in mortality between planned conventional management and cardiac transplant (p=0.158), patients with univentricular and biventricular circulations (p=0.408) or those transferred on ECMO vs non-ECMO transfer (p=0.337). Conclusion: Although transplant is effective for CHD patients transferred acutely to a quaternary PCICU, mortality on the waiting list is a serious issue. A carefully selected sub-group can be managed successfully with conventional surgery or medical management.